The recent jurisprudence of the CJEU on personal data retention: implications for criminal investigation in Portugal - Silveira, Alessandra (2017)
It can be concluded from the Tele2 judgment of 2016 that i) the declaration of invalidity of the provisions contained in a directive inevitably affects the legal act of transposition into the legal order of the Member States, and ii) a Member State cannot resort to the Directive 2002/58 to impose a generalised and undifferentiated obligation to conserve traffic and location data following the declaration of invalidity of Directive 2006/24. It is, therefore, urgent to draw conclusions from this recent ruling by the CJEU, which is all the more relevant because, in Member States where the transposed legislation continued to apply following the declaration of invalidity of Directive 2006/24 – as was the case in Portugal – many criminal convictions were based on the access to potentially illegitimate data. The authors seek to demonstrate what is happening in Portugal in this area and call for compliance with the jurisprudence of the CJEU – not only because the effectiveness of the European Union law is at stake, but also (and above all), the legal equality between European citizens